"Derived Multiple Allogeneic Protein Paracrine Signaling (d-MAPPS)" Enhances T Cell-Driven Immune Response to Murine Mammary Carcinoma. (15th June 2022) - Harrell, Carl Randall; Pavlovic, Dragica; Miloradovic, Dragana; Stojanovic, Milica Dimitrijevic; Djonov, Valentin; Volarevic, Vladislav
Abstract : Breast cancer is considered refractory to immunotherapy. Accordingly, there is an urgent need for the therapeutic use of new immunostimulatory agents which would enhance antitumor immune response against breast cancer cells. "Derived Multiple Allogeneic Protein Paracrine Signaling (d-MAPPS)" is a biological product whose activity is based on chemokines and cytokines that modulate homing and phenotype of immune cells. d-MAPPS contains high concentration of dendritic cell (DC) and T cell-attracting chemokine CXCL16 and potent T cell-activating cytokine IL-27 which enhance DC:T cell cross-talk in inflamed tissues. Herewith, we used 4T1 murine model of breast cancer to analyze d-MAPPS-dependent enhancement of T cell-driven antitumor immunity. 4T1+d-MAPPS-treated mice showed delayed mammary tumor appearance compared to 4T1+saline-treated animals. d-MAPPS significantly reduced tumor weight and volume and improved survival of 4T1-treated mice. Significantly increased concentration of CXCL16, IL-27, IFN- γ, and IL-17 and decreased concentration of immunosuppressive TGF- β and IL-10 were measured in serum samples and tumor tissues of 4T1+d-MAPPS-treated mice. d-MAPPS enhanced production of IL-12 and increased expression of MHC class II and costimulatory molecules on tumor-infiltrated DC, significantly improving their antigen-presenting properties. d-MAPPS in CXCL16-dependent manner promoted recruitment of antitumorigenic IFN- γ /IL-17-producing CD4+Th1/Th17 cells and in IL-27-dependent manner induced expansion of tumoricidal CD178+granzyme B-expressing CD8+CTLs and inhibited generation of tolerogenic DC, IL-10, and TGF- β -producing FoxP3-expressing T regulatory cells. In summing up, d-MAPPS, in CXL16- and IL-27-dependent manner, enhanced T cell-driven antitumor immune response and suppressed breast cancer growth in experimental mice.